2023
DOI: 10.3389/fmicb.2023.1141545
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding exogenous lignocellulose degrading bacteria during straw incorporation in cold regions on degradation characteristics and soil indigenous bacteria communities

Abstract: Low temperature is one of the bottleneck factors that limits the degradation of straw during rice straw incorporation. Determining strategies to promote the efficient degradation of straw in cold regions has become a highly active research area. This study was to investigate the effect of rice straw incorporation by adding exogenous lignocellulose decomposition microbial consortiums at different soil depths in cold regions. The results showed that the lignocellulose was degraded the most efficiently during str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Previous studies confirmed the efficacy of composite microbial systems in accelerating lignocellulose degradation (Hu et al, 2019 ; Wang Y. et al, 2023 ). In this study, bioaugmentation using a 30-mL XDC-2 culture resulted in enhanced degradation of rice straw during the initial 14 days.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies confirmed the efficacy of composite microbial systems in accelerating lignocellulose degradation (Hu et al, 2019 ; Wang Y. et al, 2023 ). In this study, bioaugmentation using a 30-mL XDC-2 culture resulted in enhanced degradation of rice straw during the initial 14 days.…”
Section: Discussionmentioning
confidence: 58%
“…To accelerate the decomposition of straw, agricultural machinery operations, such as crushing and plowing, are employed, along with the application of microbial agents and organic fertilizers (Goswami et al, 2020 ). Bioaugmentation using microbial agents enhances lignocellulose degradation by introducing lignocellulolytic microbes from external sources (Wang Y. et al, 2023 ). Conversely, organic fertilizers act as biostimulants by promoting the growth and activity of native microorganisms by providing essential nutrients (Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous application of compound bacterial systems plays a positive role in the abundance and diversity of the soil-dominant bacteria, thereby changing the indigenous microbial community structure of bacteria and fungi ( Chen et al, 2021 ; Nigussie et al, 2021 ). Previous research found that adding exogenous lignocellulose decomposition microbes changed the indigenous soil microbial community structure and increased crop yield, and it also increased the functional abundance of soil microorganisms ( Phukongchai et al, 2022 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the isolation and screening of cellulose-degrading bacteria under different environmental conditions are of great significance for the of cellulose ( Gao et al, 2017 ). Currently, strains with high cellulase production have been isolated and screened from animal feces ( Dhakal et al, 2020 ), decaying wood ( Haidar et al, 2021 ), and soil ( Wang et al, 2023 ), including bacteria such as Bacillus , Thermotogales , and Bacteroidales , as well as fungi such as Trichoderma harzianum , Trichoderma viride , and Penicillium ( Weimer, 2022 ).…”
Section: Introductionmentioning
confidence: 99%